Annual Cost of Civilian EMS: An Analysis of Navy Expenditures in Southern California. (2nd November 2022) - Westcott, Sally L.; Less, Kennen; Speirs, Ian; Reilly, Erin; Litkenhaus, Michele; Walrath, Benjamin
Abstract: Objective: Southern California Naval hospitals incur substantial costs through the use of civilian emergency medical services (EMS) as they lack an internal transportation team. This study aimed to quantify the volume and the associated charges for these transports in the Southern California area as these are currently unknown. Methods: This is a retrospective analysis of de-identified billing claims accessed through the Military Health System Management Analysis and Reporting Tool (M2) system. Data collected included the number and type of transports from Naval Hospitals in the Southern California area as well as the resulting charges. Data from Naval Medical Center San Diego (NMCSD) and Naval Hospital Camp Pendleton (NHCP) were collected over the 2018 and 2019 fiscal years. Results: There were 19, 886 and 19, 014 total ambulance transports in 2018 and 2019, respectively. Of these, about a quarter (8674/38900, 22.3%) were 9-1-1 calls from the patient's home resulting in an admission at a military treatment facility or network hospital. The majority were interfacility transports (20138/38900, 51.8%). These included transports from hospital discharge to home (3900/38900, 10.0%), transfers between hospitals (1648/38900, 4.2%), transfers from an office to a hospital (1818/38900, 4.7%), and transport for medical care (11682/38900, 30.0%). A large portion of these transports were for unclear transport needs (10088/38900, 25.9%). TRICARE paid 3, 872, 057 in 2018 and 4, 004, 996 in 2019 for a total of 7, 877, 053 spent on ambulance transport over the 2 years analyzed. Outside health insurance paid 10, 217, 016 over the same timeframe for these same claims. Conclusion: The interfacility transport costs incurred between NMCSD and NHCP are substantial, possibly leaving room for cost savings to be determined by further studies.